HUBUNGAN FUNGSI KOGNITIF TERHADAP KESEIMBANGAN PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 4 JAKARTA - Nia Kurniawati; Abdurahman Berbudi BL; Ditya Rizqi Mumpuni (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background: Elderly is the final stage of the human life cycle. Physical problems often suffered by the elderly are a decrease in cognitive abilities, balance disorders, hypertension, stroke, coronary heart disease, kidney failure, diabetes mellitus, tumors, and malnutrition. Purpose: The study analyzed the cognitive relationship to balance in the elderly. Methods: The design of this study was cross sectional. This research was conducted on the elderly at Panti Sosial Tresna Werdha Budi Mulia 4 Cengkareng, West Jakarta. A sample of 125 people was taken using purposive sampling. Data analysis included univariate and bivariate using Chi Square test. Results: Distribution of normal levels of cognitive function has a good balance of 60% and the other 40% has a poor balance. Respondents who have abnormal cognitive functions have a good balance of 4% and 96% have a bad balance. Statistical tests produce p value (α = 95%) of 0.01 and the value of Odds Ratio (OR) is 16. Conclusion: There is a relationship significant between cognitive function and balance.